Biocompatibility and Biomechanical Effect of Single Wall Carbon Nanotubes Implanted in the Corneal Stroma: A Proof of Concept Investigation - Alfredo Vega-Estrada; Joaquin Silvestre-Albero; Alejandra E. Rodriguez; Francisco Rodriguez-Reinoso; Jose A. Gomez-Tejedor; Carmen M. Antolinos-Turpin; Laurent Bataille; Jorge L. Alio (Journal of Ophthalmology)
Corneal ectatic disorders are characterized by a progressive weakening of the tissue due to biomechanical alterations of the corneal collagen fibers. Carbon nanostructures, mainly carbon nanotubes (CNTs) and graphene, are nanomaterials that offer extraordinary mechanical properties and are used to increase the rigidity of different materials and biomolecules such as collagen fibers. We conducted an experimental investigation where New Zealand rabbits were treated with a composition of CNTs suspended in balanced saline solution which was applied in the corneal tissue. Biocompatibility of the composition was assessed by means of histopathology analysis and mechanical properties by stress-strain measurements. Histopathology samples stained with blue Alcian showed that there were no fibrous scaring and no alterations in the mucopolysaccharides of the stroma. It also showed that there were no signs of active inflammation. These were confirmed when Masson trichrome staining was performed. Biomechanical evaluation assessed by means of tensile test showed that there is a trend to obtain higher levels of rigidity in those corneas implanted with CNTs, although these changes are not statistically significant (p>0.05). Implanting CNTs is biocompatible and safe procedure for the corneal stroma which can lead to an increase in the rigidity of the collagen fibers.